The Kantorovich form of some extensions for the Szász-Mirakjan operators - Bărbosu, Dan; Pop, Ovidiu T.; Miclăuş, Dan (Rev. Anal. Numér. Théor. Approx., 2010)
Recently, C. Mortici defined a class of linear and positive operators depending on a certain function \(φ\). These operators generalize the well known Szász-Mirakjan operators. A convergence theorem for the defined sequence by the mentioned operators was given.Other interesting approximation properties of these generalized Szász-Mirakjan operators and also their bivariate form were obtained by D. Bărbosu, O. T. Pop and D. Miclăuș.In the present paper we are dealing with the Kantorovich form of the generalized Szász-Mirakjan operators. We construct the Kantorovich associated operators and then we establish a convergence theorem for the defined operators. The degree of approximation is expressed in terms of the modulus of continuity. Next, we construct the bivariate and respectively the GBS corresponding operators and we establish some of their approximation properties.